The Productivity Puzzle in Invasion Science: Declining but Persisting Gender Imbalances in Research Performance. (12th October 2022) - Campbell, Sara E; Simberloff, Daniel
Abstract: We analyzed 27, 234 publications published since the rise of the field of invasion science in 1980 to evaluate the presence of gender differences in research productivity, the extent of collaboration, and the research impact of those differences. Our analysis revealed significantly fewer female than male authored publications, both per capita and as a group, and the underrepresentation of women as first and single authors persists despite improvements in the gender gap. At the current rate of increase, gender parity in first authorship will not be achieved until 2100, and men will continue to constitute the principal voice of first or single authors in invasion science. Women collaborate with fewer coauthors and are cited less frequently than men, on average, which may influence recruitment and retention to more senior academic positions. These gender disparities in this aspect of research performance suggest that, although the gender gap is lessening, women experience barriers in invasion science.